Investigation of the effective components of the flowers of Trollius chinensis from the perspectives of intestinal bacterial transformation and intestinal absorption. (1st January 2017) - Guo, Lina; Qiao, Shanshan; Hu, Junhong; Li, Deli; Zheng, Shiqi; Shi, Duozhi; Liu, Junxiu; Wang, Rufeng
Abstract: Context: The flowers of Trollius chinensis Bunge (Ranunculaceae), used for respiratory tract infections, mainly contain flavonoids, phenolic acids, and alkaloids; however, the effective components are debatable because of their unclear in vivo activities. Objective: This study investigates the effective components from the perspectives of biotransformation and absorption. Materials and methods: Both single person derived- and multiple people-derived intestinal florae were used to investigate the biotransformation of aqueous extract of the flowers of T. chinensis (AEOF) at the concentrations of 15.0, 30.0, and 60.0 mg/mL, respectively, for 72 h. Both human colon adenocarcinoma cell line (Caco-2) monolayers and everted gut sacs were employed to evaluate the intestinal absorption of the intestinal bacterial transformed AEOF at the concentrations of 10, 20, and 30 mg/mL, respectively, for 180 min. Results: 2″- O -β-l -Galactopyranosylorientin, orientin, vitexin, quercetin, veratric acid, proglobeflowery acid, and trolline in AEOF were not transformed by intestinal bacteria, while isoquercetin and trollioside were completely transformed. The Papp values of 2″- O -β-l -galactopyranosylorientin, orientin, and vitexin calculated based on the experimental data of intestinal absorption were at the levels of 10 −5, whereas those of veratric acid, proglobeflowery acid, and trolline were at 10 −4 . The mass ratio of flavonoids to phenolic acids to alkaloids changed from 16:10:7 to 9:12:8 before and after absorption. Discussion and conclusion: The dominant position of flavonoids was replaced by phenolic acids after absorption. In addition to flavonoids which are usually considered as the dominant effective ones, phenolic acids and alkaloids should be also very important for the efficacy of these flowers.